The Influence of Leadership and Organizational Culture on Employee Performance Through Employee Loyalty at the Prestasi Cendikia Foundation, Bekasi - Yahya, Surono; Ali, Hapzi; Sasanti Munir, Ningky (Dinasti International Journal of Digital Business Management, 2024)
The aim of this research is to analyze the influence of leadership and organizational culture on performance through employee loyalty at the Bekasi Prestasi Cendikia Foundation." This research focuses on two independent variables (X), one dependent variable (Y) and one intervening variable (Z). This research is quantitative research using a questionnaire aimed at employee respondents at the Bekasi Prestasi Cendikia Foundation. Sampling in this research was carried out using the saturated sample method with a sample size of 105 respondents. The design used in this research is hypothesis testing using Structural Equation Model (SEM) - Smart PLS 4.1. The results of this research provide an overview of the Smart PLS 4.1. statistical test with the results; 1) Leadership does not have a positive and significant effect on performance with a p-value of 0.928. 2) Organizational culture does not have a positive and significant effect on employee performance with a p-value of 0.289. 3) Leadership has a positive and significant effect on employee loyalty with a p-value of 0.012. 4) Organizational culture has a positive and significant effect on loyalty with a p-value of 0.035. 5) Employee loyalty has a positive and significant effect on employee performance with a p-Value of 0.000. The indirect hypothesis 6) Leadership has a positive and significant effect on performance through the mediation of employee loyalty, getting a P-Value of 0.043. 7) Organizational culture does not have a positive and significant effect on performance through the mediation of Motivation to get a P-Value of 0.063. This research has several limitations, namely that it only focuses on four variables, namely one dependent variable, one intervening variable and two independent variables. The research location is still limited to the at the Bekasi Prestasi Cendikia Foundation and uses a very simple research model. Future researchers are advised to use other variables that can improve performance such as productivity, work quality, efficiency, innovation, attendance rate, error rate, goal achievement, customer satisfaction, competence, task completion rate, responsibility, teamwork and others. It is recommended to expand the research sample or involve a wider study area so that the generalization of the results can be strengthened. The research method is recommended to combine various qualitative and quantitative research methods to obtain a more comprehensive understanding.